Constituent year effect in international handball at high level - Gutiérrez Aguilar, O.; Saavedra Garcia, M.; Fernández Romero, J. J. (Journal of Human Sport & Exercise, 2017)
The criterion used by the International Handball Federation for the admission of participants in the Championships at junior levels is based on the ascription of players born during two consecutive years in the same category, moving afterwards this period of two years have finished, all together to next category. The sample is composed of 2,117 handball players. The data collected for the analysis were taken in base to the gender, born date and the level of the competition. Differences among this two has been calculated through the binomial test, comparing equal proportion. There weren`t significant differences found between male and female senior categories, although in all categories more players have been found, with very significant differences, born in even-numbered years than in odd years.